Recency Bias : Impact of Market News on Stocks - Dey, Kushal; Singh, Ayush (Indian Journal of Research in Capital Markets, 2022)
Sentiments run financial markets in the short term and fundamentals in the long term. News affects the market participants’ sentiments, thus impacting stock behavior. The primary focus of this research was to study the impact that news has on a stock by analyzing the price change, volume, and shareholding patterns of the different groups of investors. In our study, we have categorized news into four different groups — news relating to management and directors, news relating to government policies and regulations, news pertaining to investors, and news relating to business activities to see how different news affects stocks. We found that after a piece of news becomes public, there is a sharp movement in the stock price, and the volume rises multiple times, making the stock highly volatile. However, the stock price generally continues to move in the same direction for the next few days. From the study of the shareholding pattern, we found that when there is a significant change in holdings, the retail and institutions are on the opposite sides, showing how different groups of investors react differently to the news. Our research will help investors and traders make better decisions by giving an idea of the stock behavior after the news. The study also opens further research opportunities into investor behavior and the different patterns of stock behavior after the news.